ADDITIONS TO THE VASCULAR FLORA OF THE UTRISH STRICT NATURE RESERVE, NORTHWEST CAUCASUS - Mikhail Kozhin (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2017)
Information about 10 species new for the Utrish Reserve (Acer tataricum L., Alyssum umbellatum Desv., Centaurea micrantha S. G. Gmelin, Linaria simplex L., Hippuris vulgaris L., Iberis taurica DC., Lycopersicon esculentum Mill., Orobanche dalmatica (G. Beck) Tzvelev, Trifolium retusum L., Ventenata dubia (Leers) Coss.) and about some species rare in the reserve is provided.